2020
DOI: 10.1002/trc2.12116
|View full text |Cite
|
Sign up to set email alerts
|

Validation of SATURN, a free, electronic, self‐administered cognitive screening test

Abstract: Background Cognitive screening is limited by clinician time and variability in administration and scoring. We therefore developed Self‐Administered Tasks Uncovering Risk of Neurodegeneration (SATURN), a free, public‐domain, self‐administered, and automatically scored cognitive screening test, and validated it on inexpensive (<$100) computer tablets. Methods SATURN is a 30‐point test including orientation, word recall, and math items adapted from the Saint Louis Universi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 59 publications
1
19
0
Order By: Relevance
“…The remaining 7 studies were identified as having high risk because having a quality score range between 5 and 6, with 1 study from other single/multiple cognitive tests, 4 studies from computerized test battery, 1 study from handwriting/drawing tests, and 1 study from daily living tasks and serious games. Among the high-risk studies, 5 studies rated 6 on the NOS, 4 of them did not report matching or using statistical control for age and education level [ 38 , 47 , 57 , 76 ], and 1 study did not report educational level [ 73 ]. In total, 1 out of these 5 studies did not provide the information on the method of confirming the cognitive status of normal controls, and 4 of them did not adopt the same procedure for ascertainment for control and cases [ 39 , 57 , 73 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The remaining 7 studies were identified as having high risk because having a quality score range between 5 and 6, with 1 study from other single/multiple cognitive tests, 4 studies from computerized test battery, 1 study from handwriting/drawing tests, and 1 study from daily living tasks and serious games. Among the high-risk studies, 5 studies rated 6 on the NOS, 4 of them did not report matching or using statistical control for age and education level [ 38 , 47 , 57 , 76 ], and 1 study did not report educational level [ 73 ]. In total, 1 out of these 5 studies did not provide the information on the method of confirming the cognitive status of normal controls, and 4 of them did not adopt the same procedure for ascertainment for control and cases [ 39 , 57 , 73 , 76 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among the high-risk studies, 5 studies rated 6 on the NOS, 4 of them did not report matching or using statistical control for age and education level [ 38 , 47 , 57 , 76 ], and 1 study did not report educational level [ 73 ]. In total, 1 out of these 5 studies did not provide the information on the method of confirming the cognitive status of normal controls, and 4 of them did not adopt the same procedure for ascertainment for control and cases [ 39 , 57 , 73 , 76 ]. In addition, another 2 studies rated 5 on the NOS, as they did not report matching or control age and education level and did not use the same procedure for ascertainment for control and cases [ 77 , 78 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The establishment of stroke networks using teleneurology provides early access for patients requiring thrombolysis [ 7 ]. Other explored methods of teleneurology are the utilization of self-administered questionnaires for the cognitive screening test for patients with dementia [ 23 ], evaluation of disability progression on patients with amyotrophic lateral sclerosis [ 22 ], and assessment of limitations in activities of daily living for patients with neuromuscular disease [ 20 , 21 ]. In patients with multiple sclerosis, their disability status is measured by incorporating data from wearable biosensors measuring average steps per day and applications such as Google Maps ™ that uses satellite imagery to measure the maximum walking distance [ 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that mobile self-administered versions of cognitive batteries or individual tests distinguish healthy individuals from individuals with MCI, Alzheimer's disease, or multiple sclerosis (MS), correlates with standard neuropsychological testing, and/or shows consistent performance when comparing clinic versus home administration. 88 89 90 91 92 93 94 95 96 Additionally, several large-scale, open source platforms have been developed to support the study of cognition in health and disease through self-administered tests performed at home (testmybrain.org, 97 labinthewild.org, 98 mobiletoolbox.org).…”
Section: Overview Of Digital Phenotyping Research By Behavioral Categorymentioning
confidence: 99%